Kirschsteiniothelia thailandica sp. nov. (Kirschsteiniotheliaceae) from Thailand - Sun, Ya-Ru; Jayawardena, Ruvishika S.; Hyde, Kevin D.; Wang, Yong (Phytotaxa, 2021)
A Kirschsteiniothelia species was found on decayed twigs of Ficus microcarpa collected at the Garden of Medicinal Plants in Chiang Rai, Thailand. Phylogenetic analyses of combined ITS, LSU and SSU sequence data showed the new isolate was phylogenetically distinct from other known species of Kirschsteiniothelia. Accordingly, Kirschsteiniothelia thailandica sp. nov. is described and illustrated and compared with other species in the genus.